Atividade antioxidante e determinação de fenóis totais, carotenoides, betacarotenos, licopeno e zinco em variedades branca, amarela e rosada de Manihot esculenta crantz - Silva, Regildo Márcio Gonçalves da [UNESP]; Figueiredo, Patrícia Aparecida [UNESP]; Peixoto, Erika Cosendey Toledo de Mello; Silva, Luciana Pereira (Univ Federal Uberlandia, 2014)
There are cassava varieties that present compounds as carotenoids, beta-carotene, lycopene and minerals important for human and animal health. The present study evaluated the antioxidant activity of the white, yellow and pinkish varieties of Manihot esculenta, by mean of the DPPH test and by the ferrous ion-chelating activity. Furthermore, the total phenols, carotenoids, beta-carotene, lycopene and zinc contents were also determined. Utilizing the DPPH test it was possible to find that extracts of boiled samples presented higher antioxidant activity (89.53% - pinkish) in comparison to the fresh samples (1.97% - white). For the ferrous ion-chelating test, the highest activity was found for the boiled pinkish variety extract (63.43%) and the lowest was for fresh yellow extract (17.34%) the white sample did not present activity. The highest concentration of total phenols and zinc content was obtained for the boiled pinkish variety extract 136.12 mg EAG/g of extract and 0,811ppm, respectively, in the concentration of 1000 µg/mL. The pinkish variety presented also higher quantity of pigments, including carotenoid (29.40 µg/g), beta-carotene (9.14 µg/100g) and lycopene (68.92%). According to the results obtained in this study it was possible to conclude that the yellow and pinkish varieties of M. esculenta present quantity of phenolic compounds and minerals sufficient to attribute the antioxidant activity and may thus contribute to reduce oxidative damage and be used as nutraceuticals or directly ingested in the diet to maintain good health.

Existem variedades de mandioca que apresentam compostos como os carotenoides, beta-caroteno, licopeno e minerais importantes para a saúde humana e animal. O presente estudo avaliou a atividade antioxidante das variedades branca, amarela e rosada de Manihot esculenta, por meio de teste de DPPH e pela atividade quelante de íons ferro. Além disso, o conteúdo de fenóis totais, carotenoides, beta-caroteno, licopeno e zinco também foram determinados. Utilizando o teste de DPPH foi possível verificar que os extratos de amostras cozidas apresentaram maior atividade antioxidante (89,53% - rosada) em comparação com as amostras frescas (1,97% - branca). Para o teste de atividade quelante de íons ferro, a maior atividade foi encontrada para o extrato da variedade rosada cozida (63,43%) e a menor foi do extrato da amarela in natura (17,34%) a amostra branca não apresentou atividade. A maior concentração de fenóis e de zinco foi obtida para o extrato da variedade rosada cozida 136,12 mg EAG/g de extrato e 0,811 ppm, respectivamente, na concentração de 1000 µg/mL. A variedade rosada apresentou também maior quantidade de pigmentos, incluindo carotenoides (29,40 µg/g); beta-caroteno (9,14 µg/100g) e licopeno (68,92%). De acordo com os resultados obtidos no presente estudo, foi possível concluir que as variedades amarela e rosada de M. esculenta, apresentam quantidades de compostos fenólicos e minerais suficientes para atribuir a atividade antioxidante, podendo assim, contribuir para diminuir os danos oxidativos e serem utilizadas como nutracêuticos ou diretamente ingeridas na dieta para manter a boa saúde.
Antioxidant activity and determination of total phenol contents, carotenoids, beta-carotene, lycopene and zinc in white, yellow and pinkish varieties of Manihot esculenta crantz
Keywords: Mandioca; Nutracêuticos; Sequestro de radicais livres; Processamento de Alimentos; DPPH; Folin-Ciocalteu; Cassava; Nutraceuticals; Free radical scavenging; Food Processing; DPPH; Folin-Ciocalteu